6 Can we do better in improving end of life care and symptom control in end-stage heart failure?. (5th October 2017) - Voon, V; Chew, S; Craig, C; White, D; Wong, E; Cahill, C; Meany, B; Twomey, F; Kiernan, T
Abstract : Background: End of life care (EOLC) preceding end-stage heart failure (ESHF) death is poorly described, even within the context of a HF disease management programme (HF-DMP). It is thought that extending this period of recognition may provide greater opportunity for better care, particularly specialist palliative care (SPC). Therefore, we aimed to characterize EOLC, especially symptom control, during the final year preceding ESHF deaths. Methods: All patient deaths (n=53) within University Hospital Limerick HF-DMP in 2014–2015, were identified and categorized as ESHF and non-ESHF deaths. We retrospectively compared medical record data between both groups for demographics, HF clinic visits, hospitalizations and SPC referral during 12 months preceding death. Missing data was excluded. Data were expressed as mean ± SD or %. Results: All ESHF deaths had at least NYHA III dyspnea prior to last hospitalization/HF clinic visit. None were eligible for heart transplant. No significant differences were observed between ESHF (n=21) vs Non-ESHF (n=20) deaths in terms of age, gender or nursing home admission within last year of life. Left ventricular ejection fraction in all patients was 30 ±13% with approximately a third of patients in both groups with implantable cardiac defibrillators (ICD). Within last 12 months of life, ESHF deaths had more HF clinic visits for HF symptom control with diuretics, versus non-ESHF deaths (1.2 ± 2.0 vs 0.3 ± 0.4, p=0.04). However, there were no significant between-group differences in HF and non-cardiovascular hospitalizations. In both groups, less than a quarter of patients had documented ICD deactivation discussions and less than a third of patients had documented SPC referrals, which were only initiated within the last 3 months of life. During this period, reported symptoms for control in ESHF deaths were dyspnea (86%), pain (19%), fatigue (57%) and oedema (67%), and were not significantly different to comparator group. Conclusion: A low incidence of documented SPC referral for symptom control and ICD deactivation discussions was observed during EOLC of ESHF deaths. This is despite greater HF symptom burden during final 12 months of life within the ESHF deaths group. More work is required to explore these observations, including the use of structured assessment to document such parameters.